2022
DOI: 10.3390/plants11070997
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Molecular Mechanisms of Cold and Hot Properties of Herbal Medicines

Abstract: Effective treatments for patients experiencing temperature-related symptoms are limited. The hot and cold effects of traditional herbal medicines have been utilized to treat and manage these symptoms, but their molecular mechanisms are not fully understood. Previous studies with arbitrarily selected herbs and ingredients may have produced biased results. Here, we aim to systematically elucidate the molecular mechanisms of the hot and cold properties of herbal medicines through an unbiased large-scale investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The conventional network pharmacological approach used to elucidate the molecular mechanism of herbal medicines involves the analysis of target genes and components of the herbs without considering the content of the compounds ( Li and Zhang, 2013 ; Park et al, 2022 ). However, when herbs are extracted into different solvents, the contents (including the type) of the extract differ.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional network pharmacological approach used to elucidate the molecular mechanism of herbal medicines involves the analysis of target genes and components of the herbs without considering the content of the compounds ( Li and Zhang, 2013 ; Park et al, 2022 ). However, when herbs are extracted into different solvents, the contents (including the type) of the extract differ.…”
Section: Discussionmentioning
confidence: 99%
“…EAHM materials that can effectively alleviate the accompanying systemic findings of this type of 'hot syndrome' are classified as cold properties. Conversely, EAHMs that can control cold syndrome are generally classified as hot property [105]. Recent studies exploring this topic at the molecular mechanism level have shown that EAHM, classified as a hot property, is implicated in pathways that include neurotransmitter reuptake, cold-induced thermogenesis, blood pressure regulation, and adrenergic receptor signaling.…”
Section: Implications Of Core Materials Explorationmentioning
confidence: 99%
“…Every year, studies expand on the chemical composition and properties of herbal medicines to assess the various interactions and molecular mechanisms which are associated with use of crude extracts, essential oils or compounds. [63][64][65] The main objectives of cytotoxicity and cell viability assays are to assess any potential of anticancer agents, and evaluate the deleterious side effects associated with herbal medicines which damage normal cells and organisms. [34,35] The cell-based cytotoxicity assays are widely used and Table 1.…”
Section: Introductionmentioning
confidence: 99%